Mapping network structures and dynamics of decentralised cryptocurrencies: The evolution of Bitcoin (2009–2023) - Marco Venturini; Daniel García-Costa; Elena Álvarez-García; Francisco Grimaldo; Flaminio Squazzoni (PLoS ONE, 2025)
At the beginning of July 2025, the global cryptocurrency market capitalisation reached more than $2.8 trillion, with 1 Bitcoin exchanging for more than $105,000. As cryptocurrencies are becoming part of the global financial infrastructure, monitoring their evolution is crucial for determining whether they can be considered a sustainable long-term financial exchange system. In this paper, we have reconstructed the network structures and dynamics of Bitcoin from its launch in January 2009 to December 2023 and identified its key evolutionary phases. Our results show that network centralisation and wealth concentration increased from the very early years, following a richer-get-richer mechanism. This trend was endogenous to the system, beyond any subsequent institutional or exogenous influence. The evolution of Bitcoin is characterised by three periods, Exploration, Adaptation, and Maturity, with substantial coherent network patterns. Our findings suggest that Bitcoin is a highly centralised structure, with high levels of wealth inequality and internally crystallised power dynamics, which may have negative implications for its long-term sustainability.